A Review of Postgraduate Theses on Integrating the Environmental Dimension of Sustainable Development into Curricula (Journal of Science Learning, 2026)
The aim of this study is to examine the master's and doctoral theses published between 2015 and 2024 on the inclusion of the environmental dimension of sustainable development in curricula. Document analysis method was used in the study, and 104 theses prepared between 2015 and 2024 on the environmental dimension of sustainability were included in the sample. In the descriptive analysis of the data, the findings were presented as percentages and frequencies. The findings revealed that mostly master's theses were prepared on the environmental dimension of sustainability; these studies were conducted in the field of Science courses, the keyword "environmental education" was mostly used in the studies, and most studies were published in 2019. At the same time, it was determined that the studies were mostly conducted at Gazi University, which is one of the largest public research universities located in Ankara, the capital city of Turkiye, published by the Educational Sciences Institute of the University. More studies were conducted by women using the quantitative research method, and the survey model was mostly used. The convenience sampling method was frequently preferred as a sampling method, and secondary school students were mostly included. A sample size of 0-50 was generally preferred, and scales were mostly used as data collection tools. Content analysis was mostly used as an analysis method.